(untitled) (Interdisciplinary Studies Journal, 2021)
Education is increasingly confirmed as a tool for the holistic development of the individual, which is why it has always been studied in its subtleties and methodologies. In this sense, one of the successful practices is the use of non-formal spaces. Therefore, in this paper, we revisit this issue with Pedagogy students in Manaus, aiming to discuss the possible theoretical and practical knowledge regarding teaching in non-formal spaces through the reading and analysis of scientific productions that address this discussion, as well as an understanding of the emerging situations of contact with environments external to the university. The study’s approach was phenomenological, focusing on how students perceive this alternative work environment, and since we were working with impressions and subjective instances, the approach was qualitative, although we presented the data in percentages. The research had a descriptive nature, and 24 students participated in the curricular component "Education in Non-Formal Spaces." The data collected were organized into categories and presented to the students themselves, followed by discussions on why such recurring issues appeared. The results are displayed in a table, followed by descriptive and reflective analysis.